Peningkatan Kewaspadaan Kanker Anak Mmelalui Pendidikan Kesehatan pada Orangtua Anak Prasekolah di Tk Al-Hidayah - Fitri Annisa (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2021)
The number of cancers in children always increases every year. Signs and symptoms of cancer in children tend to be more difficult to recognize because children are not able to express what they feel. It is very important to recognize the signs and symptoms of cancer in children so that the accurate treatment can be performed and the cure rate becomes greater. The health education was aimed to increase the knowledge and the awareness of preschool parents about cancer in children. The method of the health education was by carrying out lectures and discussions using laptops, LCDs, and leaflets. Evaluation was done by filling in the pre-test and post-test. The results of health education conducted on 20 participants showed an increase in post-test scores of 23.33 points. In addition, as many as 90% of participants stated that they had never received information regarding cancer in children. Government and health workers need to raise cancer awareness in children through health education to the wider community